2010
DOI: 10.1095/biolreprod.109.080739
|View full text |Cite
|
Sign up to set email alerts
|

The DSCs-Expressed CD82 Controls the Invasiveness of Trophoblast Cells via Integrinbeta1/MAPK/MAPK3/1 Signaling Pathway in Human First-Trimester Pregnancy1

Abstract: CD82 is recognized as a wide-spectrum tumor metastasis suppressor that inhibits cancer cell motility and invasiveness. At the human maternal-fetal interface, the decidua is believed to effectively limit the inappropriate invasion of trophoblasts. Here we have found the transcription and translation of CD82 in decidual stromal cells (DSCs), whereas trophoblast cells do not express CD82. The in-cell Western analysis reveals attenuation of CD82 translation in DSCs by human chorionic gonadotropin (hCG), but not by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 40 publications
1
42
1
Order By: Relevance
“…The expression of CD82 is involved in decidual transformation from human endometrial stromal cells (ESCs; Gellersen et al 2007). Moreover, our previous work has confirmed that CD82 in decidual stromal cells controls the trophoblasts invasiveness by suppressing integrinb1/mitogen-activated protein kinase (MAPK)/ ERK1/2 signal pathway in human early pregnancy (Li et al 2010). Interestingly, the decidualized ESCs support trophoblasts invasion by paracrine signals, such as HB-EGF, IL1, and LIF, which also can induce CD82 in ESCs for controlling trophoblasts invasion (Gonzalez et al 2011).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The expression of CD82 is involved in decidual transformation from human endometrial stromal cells (ESCs; Gellersen et al 2007). Moreover, our previous work has confirmed that CD82 in decidual stromal cells controls the trophoblasts invasiveness by suppressing integrinb1/mitogen-activated protein kinase (MAPK)/ ERK1/2 signal pathway in human early pregnancy (Li et al 2010). Interestingly, the decidualized ESCs support trophoblasts invasion by paracrine signals, such as HB-EGF, IL1, and LIF, which also can induce CD82 in ESCs for controlling trophoblasts invasion (Gonzalez et al 2011).…”
Section: Introductionmentioning
confidence: 85%
“…Moreover, the expression of integrins was intimately associated with the function of CD82. Our previous work has confirmed that DSCs-expressed CD82 controls the invasiveness of trophoblasts through suppressing the integrinb1/MAPK/ERK1/2 signal pathway (Li et al 2010). Therefore, we next investigated the protein levels of the invasion-relative molecules and integrins in the CD82-silenced ESCs from patients without endometriosis (nZ6).…”
Section: Cd82 Inhibits Invasion Of Escs By Downregulating Ccl2 Secretmentioning
confidence: 91%
“…For primary culture, sterile villi (nZ242, age: 26G2.01 years, gestational age: 8G0.49) or deciduas (nZ26, age: 24G 3.75 years, gestational age: 7G1.53) samples were immediately put into ice-cold high D-glucose DMEM (HG-DMEM; Gibco Grand Island, NY, NY, USA), with 1% penicillin and streptomycin in the medium. Tissues were transported to the laboratory within 30 min, and then trophoblasts and DSCs were isolated according to our previous procedures (Li et al 2010). These methods supplied about 85% cytokeratin-positive purified trophoblasts, and about 98% vimentin-positive and cytokeratinnegative DSCs.…”
Section: Tissue Collection Isolation and Culture Of Trophoblasts Andmentioning
confidence: 99%
“…Cytokeratin 7 (CK7) is a protein that specifically expressed in epithelial tissues, and is used as a maker of trophoblast in villi (Li et al 2010). Freshly isolated trophoblasts were gently washed with PBS, and then mixed with mouse anti-human CK7-FITC MAB (BD, Franklin Lakes, NJ, USA) and CCR3-APC MAB (Biolegend, San Diego, CA, USA).…”
Section: Flow Cytometry For Detecting Ccr3 On Trophoblastsmentioning
confidence: 99%
“…In the BM, mesenchymal stromal cells (BM-MSCs) support hematopoietic cell development, 1 whereas decidual stromal cells (DSCs) in the placenta promote trophoblast invasion and therefore implantation of the developing fetus. 2 DSCs are also important for the development of feto-maternal tolerance. 3,4 Stromal cells have immunosuppressive capacity, [5][6][7] which paved the way for using them in the treatment of inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%